World Bank Support to Early Childhood Development : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2020)
The sustained benefits of early childhood interventions are well established in developed countries. Early development plays a major role in subsequent school performance, health, socialization, and future earnings. For children born into poverty, the equity enhancing impact of early childhood interventions hold the promise of overcoming social disadvantages and breaking the intergenerational transmission of poverty. The World Bank’s support to early childhood development (ECD) is well aligned with the Bank’s twin goals of reducing extreme poverty and promoting shared prosperity. This evaluation by the Independent Evaluation Group examines the Bank’s design and implementation of projects across sectors supporting ECD interventions to inform future operations and provide inputs to the new Global Practices and Cross-Cutting Solutions Areas.